Mapping Magnetic Susceptibilitys as an Estimation of Heavy Metal Pollution in Topsoil along Ranomeeto-Kendari Road, Kendari City - Syamsul Razak Haraty; Erzam Sahaluddin Hasan; Putria Melinda (Program Studi Teknik Geofisika FITK UHO, 2023)
This study aims to identify and map the magnetic susceptibility values as an estimation of heavy metal contamination in the upper soil layer along the Bypass Road in Kendari City. The research employed a quantitative approach with direct measurements conducted in the laboratory. The results revealed that the magnetic susceptibility values in the upper soil layer of the Bypass Road in Kendari City ranged from 6,8 x – 1600,4 x . Additionally, the study detected the presence of heavy metals such as Nickel (Ni), Iron (Fe), Chromium (Cr), and Cobalt (Co) in the soil. The detected heavy metal contents exhibited significant variations, with Nickel ranging from 80 to 7920 ppm, Iron ranging from 38150 to 49920 ppm, Chromium ranging from 1210 to 21650 ppm, and Cobalt ranging from 140 to 850 ppm. These findings provide valuable insights into the potential heavy metal contamination along the Bypass Road in Kendari City and serve as a crucial basis for environmental mitigation and management efforts in the area. Key words: magnetic susceptibility, heavy metals, soil